Identification of the Potential for Development of the Smart Village Concept in Sungai Buaya Village, Pemulutan District, Ogan Ilir Regency - Sumarnah, Sumarnah; Kencana, Novia; Kariem, M. Qur’anul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research was carried out with the aim of identifying the potential for developing the smart village concept in Sungai crocodile village, Pemulutan sub-district, Ogan Ilir district. Then the results of the analysis and findings in the field from this research show that the potential of Sungai crocodile village is optimal enough to develop from the status of progress and independence of